2010
DOI: 10.1371/journal.pone.0011213
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Burden of Morbidity in HIV-Infected Adults on Antiretroviral Therapy in Côte d'Ivoire

Abstract: BackgroundLarge HIV care programs frequently subsidize antiretroviral (ARV) drugs and CD4 tests, but patients must often pay for other health-related drugs and services. We estimated the financial burden of health care for households with HIV-infected adults taking antiretroviral therapy (ART) in Côte d'Ivoire.Methodology/Principal FindingsWe conducted a cross-sectional survey. After obtaining informed consent, we interviewed HIV-infected adults taking ART who had consecutively attended one of 18 HIV care faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
48
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 42 publications
8
48
1
Order By: Relevance
“…This is confirmed by Tanzania data which found that increased age, female sex, obesity, and disability increased adults' OOP health expenditures significantly -and, among older adults specifically (60+), disability and visiting traditional healers increased expenditures (Brinda et al, 2014). In Cote d'Ivoire, sex, duration of ART use, education of the household head, household size and household income quintile were all significant predictors of CHE (Beauliere et al, 2010). Furthermore, rural households have been found to spend a larger proportion of their annual budgets on health care compared to urban households (7.8% and 5.7% respectively; Chuma & Maina, 2012).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…This is confirmed by Tanzania data which found that increased age, female sex, obesity, and disability increased adults' OOP health expenditures significantly -and, among older adults specifically (60+), disability and visiting traditional healers increased expenditures (Brinda et al, 2014). In Cote d'Ivoire, sex, duration of ART use, education of the household head, household size and household income quintile were all significant predictors of CHE (Beauliere et al, 2010). Furthermore, rural households have been found to spend a larger proportion of their annual budgets on health care compared to urban households (7.8% and 5.7% respectively; Chuma & Maina, 2012).…”
Section: Discussionsupporting
confidence: 59%
“…The cost of health care is not the only barrier to health-care access; there are a wide range of affordability, availability, and acceptability barriers, which affect poorer groups most severely (Macha et al, 2012). Research by Beauliere et al (2010) in Cote d'Ivoire and Rosen et al (2007) in South Africa indicate that in circumstances where ART is provided free to patients, OOP payments and CHE can be incurred due to non-ART-related medical expenses or travel costs (Beauliere et al, 2010;Rosen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients pay for non- ART drugs for opportunistic infections, non- routine tests, medical consultations, transportation, feeding and hospital stays. [3,4] The costs of these often have impoverishing effects on some households and hinder them from getting the necessary care[3] [4], especially in settings like Nigeria where payment for healthcare remains predominantly through out-of-pocket (OOP) payments. [5]…”
Section: Introductionmentioning
confidence: 99%
“…They may also experience stress due to HIV-associated stigma or anticipation of stigma 16 . Additionally, HIV-infected households often face increased levels of socioeconomic stressors due to the cost of healthcare and the impact that a chronic illness can have on the ability of family members to work 17, 18 . Research on the prevalence of perinatal depression in HIV-infected women has been limited, with the majority focused on the prenatal period 12, 13, 19-30 .…”
Section: Introductionmentioning
confidence: 99%